Demonstration: A cloud-native digital twin with adaptive cloud-based control and intrusion detection - Tärneberg, William; Gunnarsson, Martin; Kihl, Maria; Gehrmann, Christian (Electronic Communications of the EASST, 2021)
Digital twins are taking a central role in the industry 4.0 narrative. How- ever, they are still illusive. Many aspects of the digital-twins have yet to materialize. For example, to what degree will they be integrated into cloud and industry 4.0 sys- tems as well as how and if they should augment their physical counterpart. Those choices are accompanied by challenging security aspects, many of which have to be studied partially. In this paper, we present a novel digital-twin demonstrator that en- ables experimentation and advanced research on such systems. The demonstrator is cloud-native, has a distributed adaptive control system, incorporates edge and public clouds, a PLC, intrusion detection, a wireless network emulator, and an attacker.